2021
DOI: 10.1038/s41598-021-83543-z
|View full text |Cite
|
Sign up to set email alerts
|

A/H1N1 hemagglutinin antibodies show comparable affinity in vaccine-related Narcolepsy type 1 and control and are unlikely to contribute to pathogenesis

Abstract: An increased incidence of narcolepsy type 1 (NT1) was observed in Scandinavia following the 2009–2010 influenza Pandemrix vaccination. The association between NT1 and HLA-DQB1*06:02:01 supported the view of the vaccine as an etiological agent. A/H1N1 hemagglutinin (HA) is the main antigenic determinant of the host neutralization antibody response. Using two different immunoassays, the Luciferase Immunoprecipitation System (LIPS) and Radiobinding Assay (RBA), we investigated HA antibody levels and affinity in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Using LIPS (Secchi et al, 2020; Burbelo et al, 2005) we measured IgG binding to recombinant nanoluciferase tagged antigens corresponding to SARS-CoV-2 alpha, beta and gamma spike RBD and S2 domains, to HKU1 and OC43 seasonal betacoronaviruses spike S2 domains, and hemagglutinin (HA) antigen of the pandemic Ca2009 H1N1 influenza virus as previously described (Secchi et al, 2020; Lind et al, 2021) (Supplemental Figure 1). Briefly, we cloned recombinant nanoluciferase-tagged monomeric or multimeric antigens and expressed them by transient transfection into Expi293F™ cells (Expi293™ Expression System, Thermo Fisher Scientific Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Using LIPS (Secchi et al, 2020; Burbelo et al, 2005) we measured IgG binding to recombinant nanoluciferase tagged antigens corresponding to SARS-CoV-2 alpha, beta and gamma spike RBD and S2 domains, to HKU1 and OC43 seasonal betacoronaviruses spike S2 domains, and hemagglutinin (HA) antigen of the pandemic Ca2009 H1N1 influenza virus as previously described (Secchi et al, 2020; Lind et al, 2021) (Supplemental Figure 1). Briefly, we cloned recombinant nanoluciferase-tagged monomeric or multimeric antigens and expressed them by transient transfection into Expi293F™ cells (Expi293™ Expression System, Thermo Fisher Scientific Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent data by Lind et al. suggested that HA antibody responses are both qualitatively and quantitatively comparable between NT1 cases and controls, leading these authors to conclude that HA antibodies are likely not involved in the pathogenesis ( 95 ).…”
Section: Clinical and Translational Mechanistic Researchmentioning
confidence: 99%